Eleocharis pseudobulbosa, a new species of Cyperaceae from Southern Brazil (Capão Bonito, São Paulo) - Lima, Tamiris Daiane Delgado De; Gil, André Dos Santos Bragança; Trevisan, Rafael (Phytotaxa, 2014)
Eleocharis pseudobulbosa, a new species of Cyperaceae from Southern Brazil (Capão Bonito, São Paulo), is here described based on external morphological studies. This species is characterized by the presence of conspicuous stolons with straw-colored scales, forming a bulb-like structure in the growing points of the new culms; circular to oval culms in cross section; spikelets with small number of flowers [10–25(–30)]; achene small (0.6 mm long) and slightly reticulate; and stylopodium as wide as the achene. A detailed illustration and a diagnostic comparison with close morphological related species are presented.